MOBILITY POLICY AND JSPM (JOBS AND SKILLS PROVISIONAL MANAGEMENT) IN THE CAMEROON CUSTOMS ADMINISTRATION - Dr. ALOUMEDJO ZAM Thierry (International Journal of Research Science and Management, 2018)
This paper explores the connection between labor mobility, JSPM and organizational performance. Focusing on the case study of the Cameroon Customs administration. Much has been written about these concepts separately, but there is no integrated conceptual framework available for the combination of the said concepts, especially in a sub-Saharan public fiscal administration our goal here is to develop such a framework. We do this in a number of steps, starting with a presentation of the existing approaches, models, theories with respect to labor mobility, JSPM and organizational performance. This is followed by a search for the linkage between the three concepts or variables, as a starting point for an integrated model and an in-depth case study regarding the Cameroon Customs department. I continue with a research methodology based on a mixed approach i.e. qualitative and quantitative in order to address efficiently the research problem. I conclude with the presentation of recommendations and suggestions for further research. Statistical tests did indicate significant differences between the performance of firms using formal human resource planning and firms that do not. There was an indication of a positive change in performance after the initiation of human resource planning, relative to non‐users of such systems.